Analysis of the Implementation of Actuating and Controlling Functions in Handling Double Transfer Cases In The Treasurer Unit Of Jih Hospital, Yogyakarta - Anisah Indriani; Nurfauziah Nurfauziah (UNIVED Press, 2026)
This study aims to analyze the application of the actuating and controlling functions in handling double transfer cases in the vendor payment process at the Treasurer Unit of JIH Hospital Yogyakarta. The study used a qualitative approach with a case study method. Data were obtained through in-depth interviews with the Treasurer Unit Supervisor, who was selected purposively because of her direct involvement in the vendor payment process and handling of double transfer cases. Data analysis was carried out through the stages of transcription, coding, theme identification, and data interpretation. The results showed that double transfer cases occurred due to human error, particularly a lack of accuracy in checking payment documents, resulting in the double cross-check process not running optimally. Other contributing factors were the high volume of work and fatigue conditions that affected the concentration of officers. The actuating function was implemented through task division, coordination, communication, and work direction, while the controlling function was carried out through layered verification, document checking, identification of deviations, and corrective actions after errors were discovered. The implementation of both functions plays a crucial role in handling and minimizing the risk of vendor payment errors.